2020
DOI: 10.3389/fsufs.2020.00117
|View full text |Cite
|
Sign up to set email alerts
|

Men and Women in Rice Farming in Africa: A Cross-Country Investigation of Labor and Its Determinants

Abstract: Women make significant contribution to rice farming, processing, and marketing, but only have limited access to technical knowledge and technologies that can reduce their drudgery and labor bottlenecks, and provide them with additional income. Women also oversee the reproductive responsibilities. This paper comparatively investigates the role of women in rice farming across four countries (Burkina Faso, Côte d'Ivoire, Madagascar, Sierra Leone) by examining the labor time distribution and its resulting income f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Some women may have been reluctant in participating in the learning-by-doing phase, but many complained about the fact that they were mostly assigned the reproductive tasks during the practical on-farm demonstrations, fetching water and cooking food, so that they were not able to focus on the real training in the field. Time constraints generally faced by women because of their reproductive activities may also have prevented them to fully participate in the practical on-farm demonstration trainings (Kinkingninhoun Medagbe et al, 2020;Truong and Yamada, 2002). In addition, male farmers were found to have a better understanding of the trainings' contents than female farmers due to their higher level of formal education or schooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some women may have been reluctant in participating in the learning-by-doing phase, but many complained about the fact that they were mostly assigned the reproductive tasks during the practical on-farm demonstrations, fetching water and cooking food, so that they were not able to focus on the real training in the field. Time constraints generally faced by women because of their reproductive activities may also have prevented them to fully participate in the practical on-farm demonstration trainings (Kinkingninhoun Medagbe et al, 2020;Truong and Yamada, 2002). In addition, male farmers were found to have a better understanding of the trainings' contents than female farmers due to their higher level of formal education or schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Complex and gender-biased technologies are specifically affected (Hörner et al, 2022). The non-consideration of gender issues in the development and dissemination of agricultural technologies (Addison et al, 2019), the lack of female extension agents (Lugman et al, 2018;Ragasa et al, 2013), time constraints faced by women compared to men (Kinkingninhoun Medagbe et al, 2020;Samee et al, 2015;Truong and Yamada, 2002), extension agents mainly talking to male farmers and household heads, who are mostly men (Agboh-Noameshie et al, 2013;Lamontagne-Godwin et al, 2018;Theriault et al, 2017;World Bank and IFPRI, 2010) are the main factors restricting women's access to extension services. Gender inequalities in access to technologies contribute to global hunger and food insecurity (Njuki et al, 2016;World Bank, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, rice production is perceived to be a labor-intensive and tedious activity, which explained why rice production in southern Ghana was dominated by men, despite there being equal gender distribution in the household surveys (Asante, Asante, Acheampong, Wiredu, et al, 2013). Rice processing, including parboiling, was exclusively done by women and girls in central Benin (Zossou et al, 2010), as well as in Ivory Coast, Madagascar, Sierra Leone, and southwest Burkina Faso (Medagbe et al, 2020). However, a different study in the same region of southwest Burkina Faso showed that rice farming was mostly the responsibility of women farmers, where they accounted for 83% of the surveyed farmers in the Cascades region.…”
Section: Discussionmentioning
confidence: 99%
“…In Burundi, men rice farmers are mostly engaged in pesticide application, harvesting, and selling paddy rice, given their role as the head of the family, while women farmers are involved in land preparation, weeding, and rice trading after milling. A study conducted in different African rice-growing countries revealed that most women rice farmers do not necessarily spend more time when compared with men in rice cultivation (Medagbe et al, 2020). In fact, rice production is perceived to be a labor-intensive and tedious activity, which explained why rice production in southern Ghana was dominated by men, despite there being equal gender distribution in the household surveys (Asante, Asante, Acheampong, Wiredu, et al, 2013).…”
Section: Selection Of Pvs Varieties Is Dependent On Gender Stakeholde...mentioning
confidence: 99%
“…The produce of this farming is not for sale, except in a situation where yields are in abundance [3]. Subsistence farming is a key dominant farming in sub-Saharan Africa, especially in Sierra Leone [4]. Most of these countries lack the technological advancement to undertake commercialized farming [5].…”
Section: Introductionmentioning
confidence: 99%